Comparing the periodontal clinical effect between conventional and self-ligating brackets: Systematic review and meta-analysis. - Heber Arbildo; Luis Gamarra; Sandra Rojas; Edward Infantes; Fredy Cruzado; Hernán Vásquez (Universidad de Concepción., 2018)
Introduction: Orthodontists constantly seek to reduce the duration of their provided treatments and the patient's time in the office. For this reason, different bracket systems are currently used in orthodontics; an example is self-ligating brackets (SLB) which are believed to offer advantages over conventional brackets (CB). Objective: To evaluate and compare the clinical periodontal effect of CB and SLB through a systematic review and a meta-analysis. Material and Method: A search of the literature was carried out until December 2017, in the biomedical databases: PubMed, Embase, SciELO, ScienceDirect, SIGLE, LILACS, BBO, Google Scholar and the Cochrane Central Register of Controlled Trials. The selection criteria of the studies were defined as such: randomized clinical trials, up to 5 years old and that report the clinical effects (probing depth, bleeding on probing, gingival index and plaque index) from the use of CB and SLB. The risk of study bias was analyzed through the Cochrane Handbook of systematic reviews of interventions. Results: The search strategy resulted in 12 articles, eight of which reported no difference in the reduction in probing depth, bleeding on probing, gingival index and plaque index (p>0.05) between CB and SLB. Conclusion: The literature reviewed suggests that there are no differences in the periodontal clinical effect among patients who received orthodontic treatment with CB or SLB.